Enti ecclesiastici e Tassa comunale sui rifiuti nella recente normativa e giurisprudenza nazionale (Stato, Chiese e pluralismo confessionale, 2024)
The taxation of ecclesiastical bodies for waste tax in the recent national law and jurisprudenceABSTRACT: The heterogeneity of activities that can take place in properties owned by ecclesiastical entities raises questions of considerable systemic and tax relevance. This is probably related to the uncertainty surrounding the notion of ecclesiastical bodies, so much so that it has always occupied a prominent place in the reflections of ecclesiastical doctrine. In this regard, it is important to point out how the notion of ecclesiastical bodies indicates a category proper to the state system and not to the canonical system such that, in addition to the widespread Catholic entities, it also concerns those of different cults, so that no disparity of treatment or undue favor towards any particular denomination is configured. From a tax-law perspective, the subjective category of ecclesiastical entities does not identify a monolithic legal species of the subjective category of non-commercial entities under Article 73, paragraph 1(c) of the TUIR, as evidenced by the existence of a articulated and complex regulatory framework. With reference to this aspect, it looms interesting to examine the discipline concerning the waste tax for the ecclesiastical bodies in the light of concrete application.SOMMARIO: 1. Introduzione - 2. Brevi considerazioni sull’esordio e la nature giuridica della TARI - 3. La Convenzione tra Italia e Santa Sede in materia di scambio di informazioni fiscali - 4. Il percorso argomentativo seguito dalla giurisprudenza di Cassazione in tema di esenzione ai fini TARI per gli enti ecclesiastici - 5. Notazioni conclusive